2019
DOI: 10.3389/fchem.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approaches for Modeling the Effect of the Electrode Potential in the SERS Vibrational Wavenumbers of Pyridine Adsorbed on a Charged Silver Surface

Abstract: Vibrational wavenumbers of pyridine adsorbed on a silver electrode have been correlated to the calculated ones from different theoretical approaches based on DFT methods. The vibrational tuning caused by the electrode potential has been simulated by means of pyridine-silver clusters with different densities of charge or, alternatively, under applied external electric fields. Both methodologies predict correctly a qualitative red-shift of the vibrational wavenumbers at negative potentials. As a result, harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 44 publications
7
31
1
Order By: Relevance
“…For instance, experimental shifts of 6, 4, and 6 cm −1 are observed for the most intense bands assigned to 8a, ν(CX), and 12 fundamentals, respectively. These small vibrational shifts are similar to those recorded in the electrochemical SERS spectra of pyridine [36].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…For instance, experimental shifts of 6, 4, and 6 cm −1 are observed for the most intense bands assigned to 8a, ν(CX), and 12 fundamentals, respectively. These small vibrational shifts are similar to those recorded in the electrochemical SERS spectra of pyridine [36].…”
Section: Resultssupporting
confidence: 81%
“…This general behaviour is roughly reproduced by the calculated results predicted for the two Ag–N complexes, which show, for the abovementioned normal modes, overestimated wavenumber shifts of 15, 3, and 23 cm −1 , respectively, in the case of Ag 2 –N or even larger, 28, 10, and 40 cm −1 , respectively, when the molecule is bonded to a single silver cation with a larger positive density of charge (Ag + –N). The overestimation of the calculated wavenumber shifts upon adsorption on neutral silver clusters has been already reported and can be corrected by a factor of 0.66 at this level of theory [36], which improves the agreement between experimental and calculated results. However, the calculated wavenumber shifts of the two Ag–CN complexes just predict the opposite trend to the experiment values.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, it has been observed [ 40 , 41 ] that, in the first step of silver reduction, the formation of both (Ag ) and (Ag ) occurs; consequently, for the first time, DFT calculations on the AZ (monoanionic) and AZ (dianionic) species interacting with these clusters were carried out for the first time. It has been observed that DFT calculations performed on model systems made up by the adsorbate bound to a single Ag or small charged cluster are suitable to simulate the active sites present on silver nanostructured surfaces [ 25 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 48 ]. This approach has been revealed able to faithfully reproduce the SERS spectral features of several systems [ 38 , 39 , 42 , 43 , 47 , 49 , 50 , 51 , 52 , 53 , 54 ], regarding both frequency positions and relative intensities, and to provide information on the chemical adsorption geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode potential tunes the overall electronic structure of the surface complex, which determines the strength of the molecular adsorption as well as the energies of the perturbed intramolecular excited states and in particular, the metal-molecule charge transfer states. Our proposal of analysis is based on DFT electronic structure calculations for selected molecule-metal clusters [15][16][17]. Thereafter, the theoretical electronic spectra [18][19][20] computed on the basis of the resonance Raman vibronic theory are compared with the experimental SERS in order to detect the presence of resonant Raman processes of different types.…”
Section: Introductionmentioning
confidence: 99%